The Role of Women in the Irish National Movement 1900-1916 - Suhil, Athmar (Al-Adab Journal, 2024)
When writing about the history of the Irish national movement, we cannot overlook the role of Irish women, who had an active participation in supporting all the revolutions and uprisings that took place in all parts of the Irish island to get rid of the British occupation, despite the conservative nature of Irish society, which believed that the participation of Irish women In political activity, it is nothing but an act intended to disintegrate the fabric of the Irish family, and thus the disintegration of Irish society. The women decided to find organizations with clear political foundations that would adopt the demand for Irish women’s rights, especially with regard to their right to vote in elections. This is why the Irish political arena witnessed the emergence of many feminist organizations. Among them are the Irish Suffrage Association, the Feminist Land League, Daughters of Ireland, and the Irish Women’s Suffrage League. These organizations have opened the door for women to show their administrative, organizational and rhetorical capabilities.